Stackable bipolar pouch cells with corrosion-resistant current collectors enable high-power aqueous electrochemical energy storage. Issue 10 (14th June 2018) - Evanko, Brian; Yoo, Seung Joon; Lipton, Jason; Chun, Sang-Eun; Moskovits, Martin; Ji, Xiulei; Boettcher, Shannon W.; Stucky, Galen D.
Abstract : A platform for testing and scaling aqueous batteries and supercapacitors is demonstrated with a high-power/low-self-discharge zinc-bromine cell chemistry. Abstract : A critical bottleneck in the development of aqueous electrochemical energy storage systems is the lack of viable complete cell designs. We report a metal-free, bipolar pouch cell designed with carbon black/polyethylene composite film (CBPE) current collectors as a practical cell architecture. The light-weight, corrosion-resistant CBPE provides stable operation in a variety of aqueous electrolytes over a ∼2.5 V potential range. Because CBPE is heat-sealable, it serves simultaneously as both the pouch cell packaging and seal in addition to its use as a current collector. Although this non-metallic composite has a low electrical conductivity relative to metal foils, current travels only a short distance in the through-plane direction of the current collector in the bipolar cell configuration. This shorter path length lowers the effective electrical resistance, making the design suitable for high-power applications. We test the cell architecture using an aqueous ZnBr2 battery chemistry and incorporate tetrabutylammonium cations to improve the intrinsic low Coulombic efficiency and fast self-discharge of non-flow ZnBr2 cells. These devices demonstrate a cell-level energy density of 50 W h L −1 at a 10C rate (0.5 kW L −1 ), with less than 1% capacity loss over 500 cycles. A large-area (>6 cm 2 ) 4-cell stack is built to illustrate that the pouch cells are scalable to practical dimensions and stackable without sacrificing performance. The device operates in the range of 6–7 V and has an internal self-balancing mechanism that prevents any individual cell in the stack from overcharging. The results thus demonstrate both a conceptually new cell architecture that is broadly applicable to many aqueous electrolyte chemistries and a specific high-performance example thereof.